Parents Knowledge of Appropriate Teaching Practices in Elementary School Physical Education Programs - Barney, David; Pleban, Francis T. (International Journal about Parents in Education, 2023)
Having parental support in a child’s education is very important. Parents are, and can be, a valuable force when it comes to their child’s education. The purpose of this study was to investigate parent’s knowledge of appropriate practices in their child’s elementary physical education classes. The data were obtained by surveying 311 parents. Parents were asked to complete a 40-statement survey dealing with appropriate practices in elementary physical education. The data showed that parents tended to correctly identify appropriate practices in their child’s elementary physical education class. Yet, from the 40 survey statements, six statements were incorrectly answered by a majority of parents. It is hoped, if parents are more educated regarding their child’s physical education experience, then there is a greater chance they will be more willing to support, or continue to support, elementary physical education in their child’s education.